Percursos formativos e identidades laborais: o professor de sociologia do ensino médio - Pompeu, Dionas Ávila (2019)
This dissertation is part of the research and debates concerning the link between work, profession and education. The main objective of this study was to research, systematize and present the educational trajectories and the working identities of the teachers who teach the discipline of Sociology in the High School of the public-state schools of Santa Maria/RS. Having Claude Dubar as the main reference in the question of professional and social identity, which takes into consideration not only the subjectivities aspects of identity, but also the macrostructures, that is, those external and somewhat coercive elements that influence the conformation of individual self-identity, we sought to explore the current work configurations of teachers of basic education in the state of Rio Grande do Sul, more specifically those who were interviewed. To this end, it was used the application of questionnaires as well as interviews and document analysis. At the structural theoretical level, there was a debate about the forms of rationalization in the world of work - especially the more contemporary changes that occurred after the 1970s - and their particularities in the school environment. Regarding the professional aspect, we observed the forms of socialization through which individuals go through and shape their identities. It was argued that teachers interviewed in their working world experience aspects that have characteristics that approach and sometimes deviate from the four identity configurations proposed by Dubar, namely, identity outside work, craft identity, company identity and identity network. Moreover, observing the specific relationship of these professionals with Sociology, it was possible to build three types of professional identity related to the discipline: identity affiliation, identity affiliation and intermediary.